Chemogenetic tools for causal cellular and neuronal biology - Atasoy, Deniz; Sternson, Scott M. (American Physiological Society, 2018)
Chemogenetic technologies enable selective pharmacological control of specific cell populations. An increasing number of approaches have been developed that modulate different signaling pathways. Selective pharmacological control over G protein-coupled receptor signaling, ion channel conductances, protein association, protein stability, and small molecule targeting allows modulation of cellular processes in distinct cell types. Here, we review these chemogenetic technologies and instances of their applications in complex tissues in vivo and ex vivo.
WOS: 000424096200008
PubMed ID: 29351511
Keywords: Neuronal Biology; Causal Cellular; Chemogenetic Tools